If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4 (a+1) = 3 (a+1)
We simplify the equation to the form, which is simple to understand
4(a+1)=3(a+1)
Reorder the terms in parentheses
+(+4a+4)=3*(a+1)
Remove unnecessary parentheses
+4a+4=+3+*(+a+1+)
Reorder the terms in parentheses
+4a+4=+(+3a+3)
Remove unnecessary parentheses
+4a+4=+3a+3
We move all terms containing a to the left and all other terms to the right.
+4a-3a=+3-4
We simplify left and right side of the equation.
+1a=-1
We divide both sides of the equation by 1 to get a.
a=-1
| 1..2k+2.3=-0.5k+7.4 | | 13=6(5-b)+5(b-4) | | -5x+3y=15 | | 48=-7(-6b-8)+4(3-8b) | | -5(1-6m)-(4m+2)=-59 | | 7x^2+21x-38=0 | | -2(x-4)=-5(x-4) | | 8(-q-2)+3(q-3)=-20 | | y=4mx+6b | | xy+7x-2y-14= | | 2=-4(1-3k)+3(5k-7) | | y=4mx-2b | | -34+5p=-6-2(3p+3) | | 7+5=2-m | | (x-7)(x+6)=0 | | u+2= | | 3u^2-3= | | 8a+24b= | | (8x+6)+(x+5)= | | u^2-25= | | y=4mx+2b | | 3u-21= | | y=5mx-7b | | 8w+40= | | 2=-4(1-3j)+3(5j-7) | | w^2+3w-10= | | 2=-4(1-3j)+(5j-7) | | 5n^2+35n=0 | | -19=8(g-3)-5(-3+2g) | | (y^2-11y+30)(5y+10)=0 | | 2(x-2)+15=14 | | 8(n-4)-7(n+8)=-80 |